Minat Siswa Mengikuti Kegiatan Kerohanian Islam (Rohis) di Sekolah Menengah Atas Handayani Pekanbaru - Imam Mahdi; Risnawati Risnawati; Miftahir Rizqa (Departement of Mathematics Education, 2024)
This research aims to determine students' interest in participating in Islamic spiritual activities (Rohis) at Handayani Pekanbaru High School and the factors that influence it. This research was carried out at Handayani Pekanbaru High School using a quantitative descriptive method with percentages. The population of this research is all 250 Muslim students. Determination of samples from the population was carried out randomly (random sampling), namely 20% of all 50 students. The instruments in this research are questionnaires, interviews and documentation. The results of this research concluded that students' interest in participating in Islamic spiritual activities (Rohis) at Handayani Pekanbaru High School is GOOD. This can be seen from the results of the questionnaire percentage which shows a figure of 80.00%. There are two factors that influence it, namely internal and external factors. Internal factors include students' healthy physical condition, sufficient attention, strong interests, supported by talent and self-motivation. Meanwhile, external factors include appropriate methods and a democratic attitude of supervisors as well as the availability of adequate facilities and tools to support activities and a conducive environment.